Inclusion of Saccharomyces cerevisiae var. boulardii RC009 and Pediococcus pentosaceus RC007 as a Probiotic Additive in Pigs’ Postweaning Diets and Its Effect on Meat Composition, Carcass Characteristics, and Fatty Acids Profile after Slaughter - J. Parada; A. Magnoli; V. Alonso; L. Diaz Vergara; M. Corti Isgro; J. J. T. Posse; M. A. Montenegro; L. Cavaglieri (Veterinary Medicine International)
The postweaning is recognized as one of the most challenging stages of pig growth that can affect their lifetime productivity. The aim of the study was to evaluate the inclusion of Saccharomyces cerevisiae var. boulardii RC009 and Pediococcus pentosaceus RC007 as a probiotic additive in pigs’ postweaning diets and its effect on meat composition, carcass characteristics, and fatty acids profile after slaughter. The following three treatments (550 animals each) were included: T1: control balanced diet (CD), T2: CD with S. boulardii RC009 (1 × 109 CFU/kg feed), and T3: CD with P. pentosaceus RC007 (1 × 109 CFU/kg feed). The additive was administered throughout the postweaning phase (49 d), and then the pigs were moved to a fattening house where they no longer received probiotics in the feed. At 115 ± 5 kg, the animals were transferred to the slaughterhouse. Analyses of carcass composition, muscle depth, protein content, total fat and ash, drip and cooking water loss, and fatty acids were performed. Pigs consuming the probiotic additives had improvements in some of the production parameters. According to our results, we could observe that some modifications in meat composition after slaughter were observed in the group of pigs that consumed the probiotic additives during the postweaning, which could be considered as an improvement in meat quality. Pigs consuming probiotics had higher percentages of essential omega-3 fatty acids such as linolenic acid, and pigs consuming S. cerevisiae var. boulardii RC009 increased lean percentage and reduced the eicosanoic contents in meat. Also, an improvement in water retention capacity was observed in both groups treated with probiotics. While these results are promising, further studies are needed to evaluate the possible effect of these additives closer to slaughter, as well as their combined use.